2020
DOI: 10.1002/adfm.202005362
|View full text |Cite
|
Sign up to set email alerts
|

New High‐Performance Pb‐Based Nanocomposite Anode Enabled by Wide‐Range Pb Redox and Zintl Phase Transition

Abstract: This paper describes a new, high‐performance, Pb‐based nanocomposite anode material for lithium‐ion batteries. A unique nanocomposite structure of Pb@PbO core‐shell nanoparticles in a carbon matrix is obtained by using a simple high‐energy ball milling method using the low‐cost starting materials PbO and carbon black. Electrochemical performance tests show its excellent reversible capacity (≈600 mAh g−1) and cycle stability (92% retention at 100th cycle), which are one of the best values reported for Pb‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…However, the Pb 4f peaks of NH 3 -treated TMOF-6­(Cl) were slightly shifted to a lower binding energy, suggesting the possibility of a coordination between Pb 2+ and NH 3 (Figure b). NH 3 is a stronger electron-donating molecule than H 2 O, leading to the higher electron densities locating at Pb 2+ centers and affording the red shift of Pb 4f XPS peaks. Indeed, the peak shift toward a lower binding energy was more obvious at higher NH 3 concentrations, which further evidenced the higher tendency to form Pb 2+ –NH 3 species. Raman spectroscopy of TMOF-6­(Cl) showed a low-frequency broadband at 100–180 cm –1 owing to the presence of Pb–Cl stretching and bending modes (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…However, the Pb 4f peaks of NH 3 -treated TMOF-6­(Cl) were slightly shifted to a lower binding energy, suggesting the possibility of a coordination between Pb 2+ and NH 3 (Figure b). NH 3 is a stronger electron-donating molecule than H 2 O, leading to the higher electron densities locating at Pb 2+ centers and affording the red shift of Pb 4f XPS peaks. Indeed, the peak shift toward a lower binding energy was more obvious at higher NH 3 concentrations, which further evidenced the higher tendency to form Pb 2+ –NH 3 species. Raman spectroscopy of TMOF-6­(Cl) showed a low-frequency broadband at 100–180 cm –1 owing to the presence of Pb–Cl stretching and bending modes (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the Pb and Sb based composites can also be applied as alloy anode materials. Lee et al reported a unique Pb@PbO core‐shell nanoparticles in carbon matrix as anode for LIBs 111 . Further investigation revealed the wide‐range reversible Pb redox (between Pb 2+ and Pb 4− ) and Zintl‐type Li y Pb phase transition occurred during the electrochemical lithium reaction, which provides novel insights of lithium storage mechanism for the Pb‐based alloy anode materials.…”
Section: Interface Engineering Strategies Toward Improved Performancementioning
confidence: 94%
“…A Pb@PbO−C nanocomposite was synthesized by the high-energy ball milling (HEBM) method using PbO and carbon black, as reported in our previous paper. 29 We selected PbO as the starting material because it is brittle enough to be mechanically pulverized during HEBM. The nanoparticles were then reduced to metallic Pb by carbothermal reduction with carbon black (2PbO + C → 2Pb + CO 2 ) as the continued HEBM process generated local heat.…”
Section: Synthesis and Characterization Of Pb@pbo−c Nanocompositesmentioning
confidence: 99%
“…A more detailed description of the Pb@PbO−C nanocomposite can be found in our previous report. 29 3.2. Electrochemical Performance.…”
Section: Synthesis and Characterization Of Pb@pbo−c Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation